News in brief. (Times Higher Education, 2012)
This section offers news briefs on the higher education sector. Police in Norfolk, England have finished their inquiry into the hacking of University of East Anglia emails that led to the 2009 "Climategate" scandal. The University of Southampton has received 10 million British pounds from an anonymous philanthropist, the biggest donation in its history. More than 600 people have signed an online petition complaining about delays in the processing of post-study work visa applications.